1996
DOI: 10.3758/bf03198953
|View full text |Cite
|
Sign up to set email alerts
|

The learned function of food-deprivation cues: A role for conditioned modulation

Abstract: Rats trained in one context to use stimuli arising from food deprivation as discriminative signals for shock were tested in other contexts to assess the basis of conditioned responding (i.e., freezing or behavioral immobility). In Experiment 1, discriminative control by 24-h food-deprivation cues failed to promote transfer responding in a test context that had no association with shock. This indicated that food deprivation cues had little direct excitatory power. However, transfer of behavioral control by 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A second possibility is that acquisition of the internal state-conditional task used here requires processing of both internal and external contextual cues. Davidson and Benoit (1996) have recently reported that external context does play an important role in learning this task. Specifically, subjects learn not merely that a particular internal state predicts shock but rather that an internal state experienced in a particular external context (i.e., the conditioning chamber) predicts shock.…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that acquisition of the internal state-conditional task used here requires processing of both internal and external contextual cues. Davidson and Benoit (1996) have recently reported that external context does play an important role in learning this task. Specifically, subjects learn not merely that a particular internal state predicts shock but rather that an internal state experienced in a particular external context (i.e., the conditioning chamber) predicts shock.…”
Section: Discussionmentioning
confidence: 99%
“…Using both appetitive (peanut oil, sucrose pellets) and aversive USs (foot-shock), we have found that rats readily solve this discrimination (e.g., Davidson et al, 1993; Davidson et al, 1988; Davidson et al, 1996; Seeley et al, 1995). There are two important implications of this.…”
Section: Pre-ingestive Mechanismsmentioning
confidence: 99%
“…Such learning has been demonstrated in numerous studies to be a fundamental part of processes controlling appetite and satiety (Birch et al, 1990;Booth, 1972Booth, , 1977Booth, , 1985 as well as food choice (Gibson et al, 1995). Thus, the acceptance or rejection of a food can depend on the presence of particular internal states, which, in configuration with the orosensory cues from the food, predict specific postingestive consequences (Booth, 1985;Gibson & Booth, 1989) or at least such internal states become conditioned modulatory stimuli influencing the strength of cue-consequence associations (Davidson, 1993;Davidson & Benoit, 1996). In addition, Weingarten (1983) showed that non-food environmental cues such as a light and tone, when paired repeatedly with meal delivery to hungry rats, can come to initiate meals in rats with free access to food; such contextual cues may act as occasion setters which elicit memories of the action-outcome and cue-consequence learning that occurs when food is eaten while hungry.…”
mentioning
confidence: 99%